Metastasis in renal cell carcinoma: Biology and implications for therapy - Gong, Jun (Asian J Urol, 2016)
Although multiple advances have been made in systemic therapy for renal cell carcinoma (RCC), metastatic RCC remains incurable. In the current review, we focus on the underlying biology of RCC and plausible mechanisms of metastasis. We further outline evolving strategies to combat metastasis through adjuvant therapy. Finally, we discuss clinical patterns of metastasis in RCC and how distinct systemic therapy approaches may be considered based on the anatomic location of metastasis.